In Kluyveromyces lactis a Pair of Paralogous Isozymes Catalyze the First Committed Step of Leucine Biosynthesis in Either the Mitochondria or the Cytosol - Aguirre-López, Beatriz; Escalera-Fanjul, Ximena; Hersch-González, Jaqueline; Rojas-Ortega, Eréndira; El-Hafidi, Mohammed; Lezama, Mijail; González, James; Bianchi, Michele Maria; López, Geovani; Márquez, Dariel; Scazzocchio, Claudio; Riego-Ruiz, Lina; et al. (Frontiers in Microbiology, 2020)
Divergence of paralogous pairs, resulting from gene duplication, plays an important role in the evolution of specialized or novel gene functions. Analysis of selected duplicated pairs has elucidated some of the mechanisms underlying the functional diversification of Saccharomyces cerevisiae (S. cerevisiae) paralogous genes. Similar studies of the orthologous pairs extant in pre-whole genome duplication yeast species, such as Kluyveromyces lactis (K. lactis) remain to be addressed. The genome of K. lactis, an aerobic yeast, includes gene pairs generated by sporadic duplications. The genome of this organism comprises the KlLEU4 and KlLEU4BIS paralogous pair, annotated as putative α-isopropylmalate synthases (α-IPMSs), considered to be the orthologs of the S. cerevisiae ScLEU4/ScLEU9 paralogous genes. The enzymes encoded by the latter two genes are mitochondrially located, differing in their sensitivity to leucine allosteric inhibition resulting in ScLeu4-ScLeu4 and ScLeu4-ScLeu9 sensitive dimers and ScLeu9-ScLeu9 relatively resistant homodimers. Previous work has shown that, in a Scleu4∆ mutant, ScLEU9 expression is increased and assembly of ScLeu9-ScLeu9 leucine resistant homodimers results in loss of feedback regulation of leucine biosynthesis, leading to leucine accumulation and decreased growth rate. Here we report that: i) K. lactis harbors a sporadic gene duplication, comprising the KlLEU4, syntenic with S. cerevisiae ScLEU4 and ScLEU9, and the non-syntenic KlLEU4BIS, arising from a pre-WGD event. ii) That both, KlLEU4 and KlLEU4BIS encode leucine sensitive α-IPMSs isozymes, located in the mitochondria (KlLeu4) and the cytosol (KlLeu4BIS), respectively. iii) That both, KlLEU4 or KlLEU4BIS complement the Scleu4∆ Scleu9∆ leucine auxotrophic phenotype and revert the enhanced ScLEU9 transcription observed in a Scleu4∆ ScLEU9 mutant. The Scleu4Δ ScLEU9 growth mutant phenotype is only fully complemented when transformed with the syntenic KlLEU4 mitochondrial isoform. KlLEU4 and KlLEU4BIS underwent a different diversification pathways than that leading to ScLEU4/ScLEU9. KlLEU4 could be considered as the functional orthologue of ScLEU4, since its encoded isozyme can complement both the Scleu4∆ Scleu9∆ leucine auxotrophy and the Scleu4∆ ScLEU9 complex phenotype.